Canadian perspectives on food security and plant breeding - Claire Williams; Savannah Gleim; Stuart J. Smyth (CABI Agriculture and Bioscience)
Abstract Background The broadness of biotechnology serves to connect different types of modern plant breeding techniques with the potential to improve global food security. However, the topic goes beyond the specific example consumers’ associate with the term—genetic modification. As a result, it is often unclear if consumers really know what they claim to understand and the efforts to clarify the science and reasoning behind the use of these practices is often obscured. Methods Two online surveys of 500 Canadians were conducted in 2017. Results Three-quarters of Canadians have high levels of trust in those who provide information about food, yet two-thirds believe that modern plant breeding technologies are unnatural. Conclusions Canadians lack basic knowledge about modern plant breeding practices and technologies and possess high levels of uncertainty regarding the potential for benefits or externalities to develop from the commercialization of new genome editing plant breeding technologies.